Loop permutation affects the topology and stability of G-quadruplexes - Cheng, Mingpan; Cheng, Yu; Hao, Jingya; Jia, Guoqing; Zhou, Jun; Mergny, Jean-Louis; Li, Can (Nucleic acids research, 2018)
G-quadruplexes are unusual DNA and RNA secondary structures ubiquitous in a variety of organisms including vertebrates, plants, viruses and bacteria. The folding topology and stability of intramolecular G-quadruplexes are determined to a large extent by their loops. Loop permutation is defined as swapping two or three of these regions so that intramolecular G-quadruplexes only differ in the sequential order of their loops. Over the past two decades, both length and base composition of loops have been studied extensively, but a systematic study on the effect of loop permutation has been missing. In the present work, 99 sequences from 21 groups with different loop permutations were tested. To our surprise, both conformation and thermal stability are greatly dependent on loop permutation. Loop permutation actually matters as much as loop length and base composition on G-quadruplex folding, with effects on Tm as high as 17°C. Sequences containing a longer central loop have a high propensity to adopt a stable non-parallel topology. Conversely, sequences containing a short central loop tend to form a parallel topology of lower stability. In addition, over half of interrogated sequences were found in the genomes of diverse organisms, implicating their potential regulatory roles in the genome or as therapeutic targets. This study illustrates the structural roles of loops in G-quadruplex folding and should help to establish rules to predict the folding pattern and stability of G-quadruplexes.
Keywords: Algorithms; DNA; sekvence nukleotidů; termodynamika; konformace nukleové kyseliny; G-kvadruplexy; Base Sequence; Nucleic Acid Conformation; algoritmy; G-Quadruplexes; Thermodynamics; cirkulární dichroismus; Circular Dichroism